Enhanced availability of mercury bound to dissolved organic matter for methylation in marine sediments. (1st December 2016) - Mazrui, Nashaat M.; Jonsson, Sofi; Thota, Sravan; Zhao, Jing; Mason, Robert P.
Abstract: The forms of inorganic mercury (Hg II ) taken up and methylated by bacteria in sediments still remain largely unknown. From pure cultures studies, it has been suggested that dissolved organic matter (DOM) may facilitate the uptake either by acting as a shuttle molecule, transporting the Hg II atom to divalent metal transporters, or by binding Hg II and then being transported into the cell as a carbon source. Enhanced availability of Hg complexed to DOM has however not yet been demonstrated in natural systems. Here, we show that Hg II complexed with DOM of marine origin was up to 2.7 times more available for methylation in sediments than Hg II added as a dissolved inorganic complex (Hg II (aq) ). We argue that the DOM used to complex Hg II directly facilitated the bacterial uptake of Hg II whereas the inorganic dissolved Hg II complex adsorbed to the sediment matrix before forming bioavailable dissolved Hg II complexes. We further demonstrate that differences in net methylation in sediments with high and low organic carbon content may be explained by differences in the availability of carbon to stimulate the activity of Hg methylating bacteria rather than, as previously proposed, be due to differences in Hg II binding capacities between sediments.